Endometriotic Ascites; a very rare presentation of pelvic endometriosis (2019)
A 30 year-old P0+1 lady who was referred to the gynaecology clinic on account of inability to conceive for 8 years duration and progressive abdominal distension of 2 years duration. She had a history of severe cyclical dysmenorrhoea warranting occasional hospitalization. An abdomino-pelvic ultrasound revealed marked intra-abdominal collection. The uterus and ovaries appeared normal. She subsequently had laparoscopy and drainage of 6 litres of endometriotic ascites. Both fallopian tubes were diseased. She was followed up on an out-patient basis with sub-cutaneous goserelin injections and referred for assisted reproduction.